Black female teachers : diversifying the United Sates teacher workforce - Lewis, Chance W. (Chance Wayne), 1972-; Allen, Ayana; Farinde-Wu, Abiola (Advances in race and ethnicity in education, 2017)
With the emergence of a diverse public school studentpopulation, existing literature affirms the existence of a Black teachershortage and the low representation of teachers of color in U.S. publicschools. Although there are over 3 million public school teachers, AfricanAmerican teachers only comprise approximately 8 percent of the public schoolteaching workforce. In fact, the education field is dominated by White,middle-class teachers, particularly, White female teachers. While the retention of all teachers of color is a pertinentissue, an examination of Black female teachers who can assist in diversifyingthe teaching field is timely and warranted. Despite Black females' historic role in public education and that teaching is a female-dominated profession,Black female teachers represent only 7.7 percent of the American teachingforce, while students of color represent almost 49 percent of the total studentenrolment. This important, timely, and provocative book placesrecruitment and retention of Black female teachers at the center. Thecontributions address not only the recruitment of Black female teachers butalso discuss mechanisms necessary to retain them. Thus, this collectionnot only focuses on recruiting and retaining Black female teachers for the sakeof having their representation in schools; rather, authors consider some of theimplicit (and overt) nuances that these teachers experience in schools across theUnited States.